2020
DOI: 10.2147/ijn.s250490
|View full text |Cite
|
Sign up to set email alerts
|

<p>Radiotherapy-Activated Hafnium Oxide Nanoparticles Produce Abscopal Effect in a Mouse Colorectal Cancer Model</p>

Abstract: Despite tremendous results achieved by immune checkpoint inhibitors, most patients are not responders, mainly because of the lack of a pre-existing anti-tumor immune response. Thus, solutions to efficiently prime this immune response are currently under intensive investigations. Radiotherapy elicits cancer cell death, generating an antitumorspecific T cell response, turning tumors in personalized in situ vaccines, with potentially systemic effects (abscopal effect). Nonetheless, clinical evidence of sustained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 22 publications
5
50
0
Order By: Relevance
“…All the clonogenic assays presented in this article show that NBTXR3+RT increased cancer cell death, in a dose-dependent manner, compared to the same dose of RT alone. Considering previous studies, 2 , 4 , 19 , 20 the enhancement of cell death following NBTXR3+RT treatment compared to RT alone has now been demonstrated in fifteen different cancer cell lines originating from nine different organs/tissues ( Figure 6 , Table 1 ). This also clearly demonstrates that, thanks to its radioenhancing capacity, NBTXR3 can kill any type of cancer cell.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…All the clonogenic assays presented in this article show that NBTXR3+RT increased cancer cell death, in a dose-dependent manner, compared to the same dose of RT alone. Considering previous studies, 2 , 4 , 19 , 20 the enhancement of cell death following NBTXR3+RT treatment compared to RT alone has now been demonstrated in fifteen different cancer cell lines originating from nine different organs/tissues ( Figure 6 , Table 1 ). This also clearly demonstrates that, thanks to its radioenhancing capacity, NBTXR3 can kill any type of cancer cell.…”
Section: Discussionmentioning
confidence: 62%
“…Indeed, the heightened release of tumor-associated antigens triggered by NBTXR3+RT treatment could play a critical role in the priming or amplification of the adaptive antitumor immune response, as recently reported in the CT26 mouse colorectal model. 20
Figure 6 Review of studies with NBTXR3. The various experiments carried out in vitro and in vivo on the various human models demonstrated the effectiveness of NBTXR3 and its capacity to treat any kind of solid tumor.
…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of hafnium oxide NP (NBTXR3, a high-Z nanomaterial with high-level electron density that increases energy dose deposit within cells) plus radiation vs. radiation alone has recently demonstrated meaningful clinical benefit in locally advanced soft tissue sarcoma by doubling pathologic response rates (16 vs. 8%) (138). Significantly, recent research has reported that radiationactivated hafnium oxide NP can augment tumor infiltrates of CD8 + T cells and generate an antitumor immune response, with systemic effect on untreated tumors on the same animals in a murine model of colon cancer (139).…”
Section: Nanoparticle-mediated Immunogenic Cell Deathmentioning
confidence: 99%
“…Due to the high atomic number of hafnium, which results in greater interaction cross-sections with ionizing radiation, resulting in more energy deposition, hafnium oxide nanoparticles have been explored for immunogenic radiosensitization. Zhang et al [44] noted that these nanoparticles, when deposited intratumorally in murine colorectal cancers, can sensitize these tumors to radiotherapy. Furthermore, these resulted in greater immune cell infiltration in the irradiated tumor as well as in distant (unirradiated) tumors.…”
Section: Radiosensitizersmentioning
confidence: 99%